2018
DOI: 10.1039/c8tc00242h
|View full text |Cite
|
Sign up to set email alerts
|

Photonic hydrogels for the ultratrace sensing of divalent beryllium in seawater

Abstract: Photonic hydrogel sensing materials functionalized with 9-crown-3 are fabricated by a two-step process for the sensitive and selective detection of ultratrace Be2+ ions in seawater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…Hydrogel-based PhC sensors are generally polymerized nonclose-packed colloidal crystals or inverse opal hydrogels, 47,97 where the polymer networks are either covalently functionalized with the probe molecules, or infiltrated with functional nanoparticles (e.g., CDs). Once target analytes diffuse into the functionalized PhC hydrogels, they can react with probes, leading to a change in hydrogel volume and thereby an optical response.…”
Section: Lattice-spacing-induced Sensingmentioning
confidence: 99%
“…Hydrogel-based PhC sensors are generally polymerized nonclose-packed colloidal crystals or inverse opal hydrogels, 47,97 where the polymer networks are either covalently functionalized with the probe molecules, or infiltrated with functional nanoparticles (e.g., CDs). Once target analytes diffuse into the functionalized PhC hydrogels, they can react with probes, leading to a change in hydrogel volume and thereby an optical response.…”
Section: Lattice-spacing-induced Sensingmentioning
confidence: 99%
“…Hypo blood samples (hypoCa-1 and hypoCa-2, concentrations of Ca 2+ are reduced), normal serum, and hypercalcemic blood sample (hyperCa, concentration of Ca 2+ is increased) give rise to different colorimetric signals. Such recognition of metal ions in complex microenvironment is of importance for practical applications and has been achieved with different structural color sensors [67,69]. Ultrahigh sensitivity with microscale sensors is desirable but still challenging for detecting the trace amount of metal ions in real-time health and environment monitoring and disease prescreening.…”
Section: Ph and Ionsmentioning
confidence: 99%
“…Since the first demonstration by Asher and co-workers in which PCs were combined with intelligent hydrogels that regulate photonic band gaps by expanding or shrinking, 121 a variety of biosensors based on PC hydrogels (PCHs) have been reported, with the potential to be developed into POC devices for the detection of many types of biomarkers, such as glucoses, lectin protein, kinases, circulating tumor cells, hazardous ions, mycotoxins, Candida albicans and nucleic acids. 113,122–131 Such innovative studies have clearly demonstrated the effectiveness of structural color-based strategies in the development of novel POC devices. Current PCH biosensors, however, are all designed to immobilize only the probe molecules into hydrogels.…”
Section: Optical-based Poc Detectionmentioning
confidence: 99%